Real Time Power Flow Monitoring in a PLL Inverter Based PV Distributed Generation System - Bayrak, Gokay; Kabalci, Ersan; Cebeci, Mehmet (Ieee, 2014)
Solar cell technology has been developed rapidly in recent years, and in parallel of the photovoltaic (PV) systems becoming widespread in power generation systems, in all around the world, there have been some requirements about the integration of PV distributed generation (DG) systems into the traditional generation systems. One of these requirements will be monitored PV based DG systems and also adopting PV based DG systems to the present power system is another significant subject. In this study, an experimental monitoring system was introduced for grid connected PV power generation systems by using Labview and its useful and effective tools. The simulation of the proposed grid connected PV system test-bed is created by using Simulink where each part of the system is modelled separately. A phase locked loop (PLL) tracks the grid and inverter voltages in order to match the outputs at the same intervals in the simulation. In the laboratory, 1 kWp installed power grid connected PV array was set up, and a PLL based inverter was used as a power conditioning unit. A data acquisition (DAQ) card and developed electrical measurement circuits were used for monitoring the real time power flow in the developed PV system. Parameters and parameter changes at current, voltage and generated power in PV system acquired from the system, and these parameters were monitored in real time thanks to the Labview DAQ card. Output voltage, output current and power generated from the PV system were also monitored with developing Labview software. All the experimental results obtained from the PV power generation system were explained detailed in the paper. Proposed real time monitoring system is robust and reliable for grid connected PV based DG systems, and it can be adapted easily to other PV power generation systems.
16th International Power Electronics and Motion Control Conference and Exposition (PEMC) -- SEP 21-24, 2014 -- Antalya, TURKEY
Keywords: grid connected PV system; distributed generation; PLL; real-time power flow monitoring; data acquisition